Strength Characteristics of M40 Grade Concrete using Waste PET as Replacement for Sand - S. O. A. Olawale (Nigerian Journal of Technological Development, 2021)
The wide variety of industrial and domestic applications of plastic products has fuelled a global trend in their use. The vast amount of plastic items that are discarded after use, on the other hand, pollutes the environment. In light of this, the current study investigated the use of Polyethylene Terephthalate (PET) as substitute for natural sand in concrete production.  Locally sourced river sand was replaced with industrially ground waste PET in proportions of 4 to 20% at a step of 4% by the weight of natural sand whereas other concrete constituents (cement, granite, water-cement ratio and superplasticizer) were kept constant. A Grade M40 concrete with a mix proportion of 1:1:2:0.35 (cement: sand: granite: water-to-cement ratio) was used for all concrete mixes. Concrete without PET represents the control. Fresh (Slump) and hardened (compressive, split tensile and flexural) properties of the produced concrete were assessed using standard testing methods. The results showed that the slump of concrete decreased by 1.8% and 12.5% with an increase in PET content from 0 to 20%. The 28-day compressive strength of concrete containing PET was lower than the control. However, concrete with 4% PET compared considerably well with control with the compressive strength value exceeding the target strength of 40 N/mm2 while concretes containing PET beyond 4% had compressive strength below the target strength. The split tensile strength of concrete containing 4% PET was higher than that of the control but exhibited lower flexural strength than the control at the age of 28 days. It was concluded that the reuse of PET as a substitute for natural sand as an alternative waste disposal solution for eco-friendly concrete development and attainment of a pollution-free environment is viable.